2020
DOI: 10.1136/jmedgenet-2020-107299
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic-specific BRCA1/2 variation within Asia population: evidence from over 78 000 cancer and 40 000 non-cancer cases of Indian, Chinese, Korean and Japanese populations

Abstract: BackgroundGermline mutation in BRCA1 and BRCA2 (BRCA) is genetic predisposition for breast and ovarian cancer. Identification of mutation carriers is a critical step to prevent and treat the cancer in the mutation carriers. Human BRCA variation has been well determined as ethnic-specific by studies in Ashkenazi Jewish, Polish and Icelandic populations in the 1990s. However, sufficient evidence is lacking to determine if ethnic-specific BRCA variation is also present in Asia population, which is the largest and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…The spectrum of gBRCA1/2 variants also varies across different ethnic groups; importantly, there is a relatively high frequency of variants of uncertain significance in Asian patients [15]. To investigate this further, a recent study analyzed over 78,000 samples from cancer patients and 40,000 samples from non-cancer patients in Indian, Chinese, Korean, and Japanese populations, and found that over half of the BRCA variants identified were Asian specific [16]. Currently, there is also a paucity of data regarding the use of PARP inhibitors, including talazoparib, in Asian patients, owing to the predominance of Western patients in some breast cancer clinical trials [17][18][19].…”
Section: The Prevalence Of Brca1 and Brca2 Mutations In Unselected Asmentioning
confidence: 99%
“…The spectrum of gBRCA1/2 variants also varies across different ethnic groups; importantly, there is a relatively high frequency of variants of uncertain significance in Asian patients [15]. To investigate this further, a recent study analyzed over 78,000 samples from cancer patients and 40,000 samples from non-cancer patients in Indian, Chinese, Korean, and Japanese populations, and found that over half of the BRCA variants identified were Asian specific [16]. Currently, there is also a paucity of data regarding the use of PARP inhibitors, including talazoparib, in Asian patients, owing to the predominance of Western patients in some breast cancer clinical trials [17][18][19].…”
Section: The Prevalence Of Brca1 and Brca2 Mutations In Unselected Asmentioning
confidence: 99%
“…The previous study based on the data from the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA) has identified that there was a substantial difference in variant type, frequency, and location by geographical region and race or ethnicity [ 10 ]. In addition, over 50% of Asian BRCA variants were Asian-specific, and even among Asian populations (Indian, Chinese, Korean, and Japanese populations) there were significant differences [ 11 ]. For these reasons, we assumed that the patterns and effects of BRCA1 or BRCA2 pathogenic variants related to breast or ovarian cancer in Korean are different than those of other populations (not only non-Europeans but also other Asians).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the data are based on European populations. Although it has been suggested that cancer risk and genetic variation vary by populations [ 10 , 11 , 12 ], there is still a lack of research on non-European populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic nephropathy (DN) is a frequent type of diabetic complication which results from permanent uncontrolled diabetes, and it usually causes end-stage renal diseases (ESRD). 1,2 In addition, DN also results in increased thickness of the basement membrane, glomerular sclerosis and renal fibrosis. 3,4 Nowadays, the main treatment of DN is drug therapy, 5 while the effect of drug therapy remains limited.…”
Section: Introductionmentioning
confidence: 99%